Subareolar breast abscess in male patients: a report of two patients with a literature review - Takashi Kazama; Isao Tabei; Chikako Sekine; Naotake Funamizu; Shinji Onda; Tomoyoshi Okamoto; Hiroshi Takeyama; Toshiaki Morikawa (Surgical Case Reports, 2017)
Abstract Background Subareolar breast abscess (SBA) is a rare infectious disease of the breast in male patients. Case presentation Herein, we report two male patients with SBA. Patient 1 was initially diagnosed with a malignant tumor based on imaging findings; ultrasonography revealed a hypoechoic mass with blood flow. Patient 2 was diagnosed with inflammatory changes to his nipple; ultrasonography findings supported the diagnosis with an irregular hypoechoic mass with blood flow. Both patients received a cytological or histological biopsy preoperatively, which showed an abscess without malignant cells. Conclusion These cases serve as an important reminder to consider complete resection of the tumor including the responsible mammary duct (tumor and duct resection (TDR)) for curative therapy of SBA.